1977
DOI: 10.1021/bk-1977-0040.ch017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Zeolite A Synthesis

Abstract: Experiments utilizing several different characterization techniques as a function of time, including chemical analyses,Raman spectra, x-ray diffraction, sorption and particle size measurements, have been performed to determine the mechanistic pathway in 4A synthesis.The evidence supports a mechanism involving formation and subsequent dissolution of an amorphous aluminosilicate intermediate, with solution transport from the gel to the growth surface of the crystallite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 3 publications
3
15
0
1
Order By: Relevance
“…This disruption of the US-attenuation trend can also be supported by Cundy and Cox's [29] concept of the formation of the 'pseudosteady-state intermediate' which they had referred to as 'secondary amorphous phase' occurring via solution transport mechanism during the process of evolution of order. The existence of primary (visible gel) and secondary amorphous phases had also been proposed by Angell and Flank [30]. During the nucleation period, between 120 and 150 min (see Fig.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This disruption of the US-attenuation trend can also be supported by Cundy and Cox's [29] concept of the formation of the 'pseudosteady-state intermediate' which they had referred to as 'secondary amorphous phase' occurring via solution transport mechanism during the process of evolution of order. The existence of primary (visible gel) and secondary amorphous phases had also been proposed by Angell and Flank [30]. During the nucleation period, between 120 and 150 min (see Fig.…”
Section: Discussionsupporting
confidence: 64%
“…The overall decrease in the ratio of the amount of amorphous material to the number of crystals of zeolite A shown in Fig. 8 is indicative and confirms the auto-catalytic process which suggest that the 'rate of gel dissolution must increase with the rate of consumption of growth species by increasing cumulative crystal surface area' [29,30,45].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, such studies are surprisingly rare in the literature, which is partly due to the far less developed molecular spectroscopic identification of dissolved silicate structures than that of solid silicates. There are several Raman [12][13][14][15][16][17][18][19][20][21][22][23] and IR [17,[21][22][23][24][25][26][27][28] publications which focus specifically on aqueous silicate solutions and one can also find such spectra in some zeolite synthesis related papers [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. However, only a small group from these authors has assigned certain vibrational bands to specific molecular structures like monomers or siloxane chains, rings, etc.…”
Section: Introductionmentioning
confidence: 99%
“…From those studies, the role of the solution phase in the zeolite formation mechanism became increasingly important, as evidenced by several different experiments. In this respect, Angell and Flank [46] reached some conclusions different from those reported by McNicol and coworkers [47,48] after using Raman spectroscopy, XRD, and particle size analyses. The former study was later supported by the reports by Culfaz and Sand [49] and Kacirek and Lechert [50] which concluded that the rate-determining step was the linking of silicate species to the surface of the crystal.…”
Section: Synthesis and Structurementioning
confidence: 64%